Passiflora nana, a new species in Passiflora section Decaloba (Passifloraceae) from northern Peru - Macdougal, John M.; Esquerre-Ibañez, Boris (Phytotaxa, 2020)
A new species of Passiflora L. endemic to cloud forest in northern Peru, P. nana, is described and illustrated from living and herbarium material. The new species is similar to the Colombian  P. erythrophylla in flower and Ecuadorian P. hirtiflora in vestiture. The indument is pilose to hispidulous throughout with long straight white trichomes, and the plant is short, less than 2.5 m long, with a very small flower ca. 1.5 cm diam. It is placed in subgenus Decaloba supersection Decaloba section Decaloba.